Expansion and pathogenic activation of skeletal muscle–resident macrophages in mdx 5cv /Ccr2 −/− mice - Yinhang Wang; Xingyu Wang; Salam Alabdullatif; Sachiko T. Homma; Yuriy O. Alekseyev; Lan Zhou (Proceedings of the National Academy of Sciences, 2025)
Infiltrating macrophages contribute to muscle dystrophic changes in Duchenne muscular dystrophy (DMD). In a DMD mouse model, mdx 5cv mice, CC chemokine receptor type 2 (CCR2) deficiency diminishes Ly6C hi macrophage infiltration by blocking blood Ly6C hi inflammatory monocyte recruitment. This is accompanied by transient improvement of muscle damage, fibrosis, and regeneration. The benefit, however, is lost after the expansion of intramuscular Ly6C lo macrophages. To address the mechanisms underlying the Ly6C lo macrophage expansion, we compared mdx 5cv /Nur77 −/− and mdx 5cv /Ccr2 −/− /Nur7 −/− mice with mdx 5cv and mdx 5cv /Ccr2 −/− mice, respectively, and found no evidence to suggest Ly6C lo monocyte recruitment by dystrophic muscles. Single-cell RNA sequencing analysis and Flt3 cre /Rosa26 LSL-YFP -based lineage tracing of macrophage origins demonstrated the expansion and pathogenic activation of muscle resident macrophages in CCR2-deficient mdx 5cv mice. The expansion was associated with increased cell proliferation, which appeared induced by colony-stimulating factor-1 (CSF-1) derived from fibro/adipogenic progenitors (FAPs). Our study establishes a pathogenic role for skeletal muscle resident macrophages and supports a regulatory role of FAPs in stimulating the expansion of resident macrophages in the DMD mouse model when the inflammatory macrophage infiltration is inhibited.